A case study of the use of technology in secondary mathematics with reference to the dimensions of learning framework - Thomson, Ian Allan (Curtin University, 2012)
In this thesis a case study was conducted which concerned the use of technology in secondary mathematics. Within a particular setting, the research evaluates the contribution that the use of technology makes to the process of learning mathematics and to students’ perceptions about learning mathematics.In the study, Year 8 students used technology to work on problems involving algebra and geometry. The students had individual access to touch screen calculators. A tablet computer attached to a digital projector was available for use in the classroom. The research was carried out by a teacher working as a participant-researcher. The students involved in the research were drawn from a group who had been selected to take part in mathematics enrichment lessons. They were extracted from their usual mathematics classes for one lesson per week over a four month period for this purpose.The study took place in a school which had committed itself to two main initiatives. One of these initiatives was to introduce technology into teaching and learning. The other initiative was to upgrade the teaching practices at the school by adopting the Dimensions of Learning framework as a pedagogical model. The tasks that the students were given to work on in the study were selected to align with different aspects of the Dimensions of Learning framework. The analysis used the Dimensions of Learning framework as a reference tool for both the design of the tasks and the outcomes of implementing them with the students.It was found that the use of technology could be productively aligned with procedural (“know how”) knowledge and declarative (“know what”) knowledge. The contribution that the use of technology made to complex reasoning processes associated with extending knowledge and using knowledge meaningfully was also evaluated. The students’ feelings about the use of technology were sometimes positive and sometimes negative but they had stronger feelings about other aspects of their experience in learning mathematics aside from the use of technology.